O desconhecido do pouco conhecido : padrão espacial de riqueza e lacunas de conhecimento em plantas (Fabales: Fabaceae) na caatinga - Pereira, Taiguã Corrêa (2016)
The biodiversity is distributed heterogeneously across the Earth. Although the discussion about which factors determine the spatial patterns of species diversity remains controversial, to know the components of biodiversity themselves is a challenge even bigger in certain regions. So, to know how much still remains to be studied or discovered is fundamental to the science, and the lack of knowledge about the species geographical distribution is known as one of the main problems faced in biodiversity research, especially in “Megadiverse” countries like Brazil. Historically, the Caatinga biome has been recognized as one of the most unknown and less valued according to its biodiversity, because the erroneous idea that the biome would have low diversity and endemism rates, and high degrees of degradation. Considering the dominance of the Family Fabaceae in the Caatinga, in both richness and abundance, we investigated the spatial pattern of Fabaceae species richness on the biome looking for determine which are the factors responsible for the spatial variation on its species richness. Moreover, we elaborated a spatial statistical model for the diversity of Fabaceae in the Caatinga, utilizing the spatial structure of the know assemblages and their environmental determinants, in order to estimate the shortfall of knowledge about the distribution (Wallacean shortfall) of the family in the Caatinga. We obtained 220,781 registers, less than 25% were valid. From these registers, we found 1,310 species in 198 genera. The predict richness vary from 92 to 283 species across the space and was better described by the sampling effort, the soil properties and the topography. With the measure of discrepancy between predicted and the observed values of species richness, we estimated the Wallacean shortfall, reaching 192 species in one single locality. The total number of species found in this work represents an expressive improvement on the know species richness of the family in the Caatinga. The selection of non-climatic factors as the main predictors of richness indicate the major influence of topography and soil on regional scale. The importance of substrate on the establishment of plant communities on the semiarid, as well. The estimated Wallacean shortfall evidences a chronical and spatially heterogeneous deficiency on knowledge of the regional flora. The persistence of such expressive gaps on the knowledge, plus the reduced coverage of protected areas on the biome shows a currently risk of significantly losses of biological diversity, with serious implications for the conservation of the biome.